Determinants of each domain of the Short Physical Performance Battery in COPD - Bernabeu-Mora R; Giménez-Giménez LM; Montilla-Herrador J; García-Guillamón G; García-Vidal JA; Medina-Mirapeix F (International Journal of COPD, 2017)
Roberto Bernabeu-Mora,1 Luz M Giménez-Giménez,2 Joaquina Montilla-Herrador,2 Gloria García-Guillamón,2 José Antonio García-Vidal,2 Francesc Medina-Mirapeix2 1Division of Pneumology, Hospital General Universitario Morales Meseguer, 2Department of Physical Therapy, University of Murcia, Murcia, Spain Background: The Short Physical Performance Battery (SPPB) is an assessment tool with good prognostic value in COPD. It includes the following: standing balance, 4 m gait speed test (4MGS), and the timed five-repetition sit-to-stand test (5STS). The specific differences in determinants between these three tasks have not been adequately characterized in COPD patients. We aimed to identify health-related, functional, and psychological determinants of each SPPB test. Methods: We conducted a cross-sectional analysis of 137 patients with stable COPD. Patients performed the SPPB, quadriceps muscle strength (QMS), exercise tolerance test (6-min walk test [6MWT]), and pulmonary function; and health-related and psychological factors, physical activity, the COPD assessment test (CAT), body mass index, age, and depression were assessed. Results: Separate multivariable regression models predicting the 4MGS, 5STS, and balance test results described 31%, 39.1%, and 12.1% of the variance for each test, respectively. QMS was negatively associated with all three tests. The 6MWT was negatively associated with the 4MGS and 5STS. Depression and age were positively associated with 4MGS scores, whereas CAT and age were positively associated with 5STS scores. Conclusion: The three SPPB tests did not provide equivalent information regarding a COPD patient’s status. The 5STS was associated with health status factors, while the 4MGS was associated with psychological factors. Keywords: COPD, muscle strength, gait speed, 6-min walk test, depression